Stable Isotope Analysis of Diet‐based Social Differentiation at Late Prehistoric Collective Burials in South‐Western Portugal. (29th January 2015) - Waterman, A. J.; Tykot, R. H.; Silva, A. M.
Abstract : In the Neolithic and Copper Age collective burials of the Portuguese Estremadura, the majority of material culture and skeletal remains are highly commingled, making it difficult for archaeologists to evaluate social status by linking individuals with specific grave goods. In these circumstances, bio‐anthropological data about individual life histories offer an additional avenue of investigation into social complexity among prehistoric communities practising collective burial. In this study, stable isotope data were gathered from 81 individuals from seven collective burial sites and one settlement, the fortified site of Zambujal, in order to determine if significant dietary differences exist within or between burials that may point to patterns of social differentiation, both at individual sites and across the region. While in general all of the sampled individuals consumed fairly homogeneous diets based on terrestrial animal proteins and C3 plants, this study found that statistically significant differences in δ 13 Cap and δ 15 N values exist between several sites, which may indicate socially differentiated consumption of meat and plants. Additionally, statistically significant differences were found in δ 15 N values between adults and juveniles, which may either be attributable to protein‐restrictive child‐feeding practices or physiological processes related to skeletal growth and development.